"La constitucionalización del derecho del adolescente mayor de 16 años a intervenir como testigo en acto testamentario" - Lema Guamani, Freddy Vinicio (2014)
This legal research, whose theme is " THE LAW OF THE MAYOR constitutionalization of TEEN 16 YEARS AS A WITNESS TO INTERVENE IN PROBATE ACT" general objective was to determine the regulatory domain of the prohibition in Article 1050 of the Civil Code does not guarantees the constitutional right of persons under 18 and over 16 yearsâ act as a witness in the solemn act of the will. To this end, this legal research is structured into six chapters. In the FIRST CHAPTER, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the research hypothesis. The SECOND CHAPTER refers to the theoretical framework, aspects: historical, doctrinal and legal. In the THIRD CHAPTER the methodology used in the research described in point; methods applied, types of research, population, sample techniques and instruments used in data collection. In the FOURTH CHAPTER the hypothesis is tested through the research findings obtained by interviewing authorities located Quevedo, plus surveys of lawyers in free practice, you know as they are violated without any regard to the rights of children to not allow them to exercise their rights. The FIFTH CHAPTER describes the conclusions and recommendations. SIX CHAPTER finally talks about the proposal, objectives, description of the' proposal, beneficiaries and social impact, etc